Interaction of phosphatidylinositol 3-kinase-associated p85 with epidermal growth factor and platelet-derived growth factor receptors. - Hu, P (1992)
One of the immediate cellular responses to stimulation by various growth factors is the activation of a phosphatidylinositol (PI) 3-kinase. We recently cloned the 85-kDa subunit of PI 3-kinase (p85) from a lambda gt11 expression library, using the tyrosine-phosphorylated carboxy terminus of the epidermal growth factor (EGF) receptor as a probe (E. Y. Skolnik, B. Margolis, M. Mohammadi, E. Lowenstein, R. Fischer, A. Drepps, A. Ullrich, and J. Schlessinger, Cell 65:83-90, 1991). In this study, we have examined the association of p85 with EGF and platelet-derived growth factor (PDGF) receptors and the tyrosine phosphorylation of p85 in 3T3 (HER14) cells in response to EGF and PDGF treatment. Treatment of cells with EGF or PDGF markedly increased the amount of p85 associated with EGF and PDGF receptors. Binding assays with glutathione S-transferase (GST) fusion proteins demonstrated that either Src homology region 2 (SH2) domain of p85 is sufficient for binding to EGF and PDGF receptors and that receptor tyrosine autophosphorylation is required for binding. Binding of a GST fusion protein expressing the N-terminal SH2 domain of p85 (GST-N-SH2) to EGF and PDGF receptors was half-maximally inhibited by 2 and 24 mM phosphotyrosine (P-Tyr), respectively, suggesting that the N-SH2 domain interacts more stably with PDGF receptors than with EGF receptors. The amount of receptor-p85 complex detected in HER14 cells treated with EGF or PDGF. Growth factor treatment also increased the amount of p85 found in anti-PDGF-treated HER14 cells, suggesting that the vast majority of p85 in the anti-P-Tyr fraction is receptor associated but not phosphorylated on tyrosine residues. Only upon transient overexpression of p85 and PDGF receptor did p85 become tyrosine phosphorylated. These are consistent with the hypothesis that p85 functions as an adaptor molecule that targets PI 3-kinase to activated growth factor receptors.